Do activities of foreign investors affect main stock exchange indices? Evidence from Turkey before and in time of Covid-19 pandemic - Mustafa Tevfik Kartal (National Accounting Review, 2020)
The net selling amount and foreign investors' retention share have been criticized due to the effects on stock exchange indices. The study focuses on the development of the main index in Turkey (XU100 index) by examining two sub-parts (i.e. before and in Covid-19 pandemic). Daily data between 01.02.2020 and 06.26.2020 are analyzed by applying the Engle-Granger cointegration test, Toda-Yamamoto causality test, and multivariate adaptive regression splines (MARS). The findings reveal that (ⅰ) net selling amount of foreign investors has an effect on the index in Covid-19 pandemic times; (ⅱ) retention share of foreign investors is influential on the index for both period; (ⅲ) there is cointegration between the index and independent variables but this relationship is not at causality level.